Gene expression and Levels of Plasma Protein Tyrosine Phosphatase Non-Receptor Type 22 (PTPN22)in Pulmonary Tuberculosis Patients and their Household Contacts in Makassar, Indonesia - Ibrahim A1,3, Djaharuddin I2 , Hidayah N1 , Subair1 , Handayani I1 , Tenriola A1 , Massi MN4,5* (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The protein tyrosine phosphatase non-receptor type 22 (PTPN22) gen,has been involved in the immune response to tuberculosis infection by affecting the inflammatory response and subsequent anti microbial immunity. This study aims to determine the PTPN22 expression and differences in the levels of PTPN22 in pulmonary TB patients (PTB) with household contacts and healthy control. Methods: We analyzed PTPN22 expression and the level of plasma PTPN22 from pulmonary tuberculosis patients (PTB), household contacts and healthy control using real time PCR and ELISA method. Results: ThirtyPTB, 30 household contacts and 30 control were involved in this study. Analysis of the assocation of PTPN22 gene expression against TB showed that PTPN22 gene expression was 7.3 times upregulated compared to household contact and 12.1 times upregulated compared to healthy controls.Levels of plasma PTPN22 in PTB: 10.0620 ng/ml, in Household contact: 6.7923 ng/ml and in control: 4.4293 ng/ These values did not differ significantly between the patients, household contact and control. Conclusion: Our study results found that PTPN22 gene expression is significantly increased in PTB than household contact and control.Levels of plasma PTPN22 in PTB patientsdid not differ significantly than in household contact and control.